P525 Patients' Perception of Risks of biologic therapy During Covid-19 Pandemic in Israel Orly Lior, Ilia Sergeev, Nahum Ruhimovich, Michal Openheim, Fabiana Benjaminov, Dan Feldman, Yehuda Ringel, Timna Naftali Division of Gastroenterology and Liver Diseases, Meir Medical Center, Kfar Saba, Israel. (27th May 2021) - Lior, O; Sergeev, I; Ruhimovich, N; Openheim, M; Benjaminov, F; Feldman, D; Ringel, Y; Naftali, T
Abstract: Background: Current inflammatory bowel disease (IBD) therapies are highly effective. However, compliance with treatment is influenced by patients' perception of benefits versus risks. Understanding these perceptions and their influence on patients' treatment decision-making is crucial for achieving compliance, especially during Covid-19 pandemic. Aim: to assess patients' perception of risks of IBD exacerbation and SARS-CoV-2 infection, and their influence on patients' decisions regarding biologic and immunosuppressive treatments during Covid-19 pandemic in Israel. Methods: A prospective internet-based survey among Meir Medical Center, IBD clinic patients. Results: 116 patients have responded. Mean age 42 (18–84), 44 (38%) males, 75 (64%) Crohn's disease, 38 (32%) ulcerative colitis, 34 (29%) with history of abdominal surgery, 47 (40%) were in remission and 9(7.5%) with severe disease. 18 (15%) patients were on Immunosuppressive and 76 (66%) on biologic treatments. Concerns of contracting SARS-CoV-2 infection: 56 (48%) patients considered their risk as equal to that of the general population whereas 53 (46%) considered it to be increased. 55% of the patients related the increase risk of COVID-19 infection to their IBD treatment, whereas 47% related it to having IBD. Patients treated with biologics were more concerned of becoming infected with SARS-CoV-2 then those who were not. There was also a significant association between depression and anxiety levels and the fear of becoming infected (r= 0.3 for depression and 0.4 for anxiety). Adherence to IBD treatment: Only 8 (7.5%) patients considered stopping their IBD treatment, and only 4 (3.7%) patients actually stopped their treatment. Patients with more severe disease were more inclined to stop their treatment compared to those with mild disease. Reasons for not stopping treatment were fear of disease exacerbation in 37 (32%) patients, and reassuring information received from medical providers, in 25 (21.5%) patients. When faced with a theoretical question of trading long-term remission versus risk of SARS-CoV-2infection, 34 (29%) patients were willing to accept a 10% infection risk for a 10-year remission Conclusion: Significant portion of the patients with IBD believe that they are at increased risk of contracting SARS-CoV-2 infection, and more than half of them related the increase risk to their IBD treatment. However, despite their fear most patients felt safe enough to continue their treatment. Patients with more severe disease and treated with biologics experienced higher levels of anxiety, depression and fear of COVID-19 infection. Identifying and addressing these fears early might increase patient's adherence to treatment and prevent the hazardous effects of discontinuation of treatment.